Immortal beloved - Rose, Bernard 1960-; Oldman, Gary 1958-; Krabbé, Jeroen 1944-; Rossellini, Isabella 1952-; Steege, Johanna ter 1961-; Golino, Valeria 1966- (Columbia TriStar Home Video, 2000)
Based on the life of composer Ludwig Beethoven. A letter found after his death leads to efforts to uncover the mystery of who was his immortal beloved
DVD release of the 1994 motion picture
Special features: digitally remastered audio and anamorphic video, director's commentary, "Beloved Beethoven" documentary, original featurette, theatrical trailer, talent files, and production notes
Special features: Widescreen version -- Digitally remastered audio and anamorphic video -- Director's commentary -- "Beloved Beethoven" documentary -- Original featurette -- Theatrical trailer -- Talent files -- Scene selections -- Production notes -- Interactive menus -- Language: English 5.1 Dolby digital ; English 2-channel Dolby surround ; Spanish -- Subtitles: English, Spanish
Früheres Copyright: 1994
Aspect ratio 2.35:1
Keywords: Beethoven, Ludwig van -- 1770-1827; Beethoven, Ludwig van / 1770-1827 / Drama; Composers / Austria / Drama; Beethoven, Ludwig van / 1770-1827; Composers; Austria; Films historiques; Films pour personnes handicapées auditives; DVD-Video discs; Romance films / Great Britain; Biographical films / Great Britain; Historical films / Great Britain; Feature films / Great Britain; Romance films; Historical films; Fiction films; Video recordings for the hearing impaired; Biographical films; Drama; Feature films; Romances; Biographical; Musical; Feature; Romance; Vidéos pour personnes handicapées auditives; Films de fiction; Films d'amour; Films biographiques; Film; DVD-Video